2021
DOI: 10.1088/2053-1591/ac432a
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of weldment mechanical properties in GMAW with robot-assisted using fuzzy logic systems

Abstract: Welding operation decides the quality of product standards in all metal work products like automobiles, aerospace vehicles, and many more. The quality of the welding process is more reliable by automating the process with robots. In this research work, the GMAW operation is automated with the “Fanuc Robot Arc mate 100iC/12” robot. The material characteristics such as ultimate tensile strength, hardness, and impact strength of weldments are predicted using a fuzzy system using triangular membership function (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…Bulanık mantığın spesifik özelliği, kümelerin sınırlarının keskin olmayışından kaynaklanır. Süreç, bulanıklaştırma, kural işleme ve karar mekanizması, durulaştırma aşamalarından oluşur (Medhi et al, 2020;Palani et al, 2020;Devendran & Ashoka Varthanan, 2021). Bulanık kümeyi ifade etmede üyelik fonksiyonları kullanılmaktadır.…”
Section: Bulanık Mantık Yöntemiunclassified
“…Bulanık mantığın spesifik özelliği, kümelerin sınırlarının keskin olmayışından kaynaklanır. Süreç, bulanıklaştırma, kural işleme ve karar mekanizması, durulaştırma aşamalarından oluşur (Medhi et al, 2020;Palani et al, 2020;Devendran & Ashoka Varthanan, 2021). Bulanık kümeyi ifade etmede üyelik fonksiyonları kullanılmaktadır.…”
Section: Bulanık Mantık Yöntemiunclassified
“…Research in this field has demonstrated the reliability of automating welding processes using robotics. For instance, a GMAW operation was automated using the 'Fanuc Robot Arc Mate 100iC/12' robot, proving the feasibility and efficiency of such systems in real-world applications [12]. The primary operational circuit consists of Arduino Mega as the microcontroller, 11 motors with varying weight capacity, MPU6050, and Proportional -Integral -Derivative (PID) controllers.…”
Section: Electronic Segmentmentioning
confidence: 99%